2006
DOI: 10.1097/01.inf.0000217370.83948.51
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inactivated Influenza Vaccine for Prevention of Otitis Media in Children

Abstract: Influenza vaccine is effective in reducing AOM and OME episodes in 6- to 60-month-old day care children, especially during influenza season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…Ozgur et al 23 showed that there was a 50.9% decrease in the incidence of AOM in a groups of children aged between 6 months and 5 years, compared to controls; this study also demonstrated a 26.7% decrease in the total number of cases of otitis media with effusion in a 6-month follow-up period.…”
Section: C) the Inactivated Influenza Virus Vaccinesupporting
confidence: 50%
“…Ozgur et al 23 showed that there was a 50.9% decrease in the incidence of AOM in a groups of children aged between 6 months and 5 years, compared to controls; this study also demonstrated a 26.7% decrease in the total number of cases of otitis media with effusion in a 6-month follow-up period.…”
Section: C) the Inactivated Influenza Virus Vaccinesupporting
confidence: 50%
“…62 Vaccine efficacy of 56% against influenza illness was documented among healthy children 3 to 9 years of age, 49 and another study determined vaccine efficacy against influenza type B and A infections of 22% to 54% and 60% to 78% among children with asthma 2 to 6 years of age and 7 to 14 years of age, respectively. 79 TIV has also been found to considerably decrease the incidence of influenza-attributable otitis media among young children, [80][81][82] although another study contradicts this finding. 63 Results have also shown the efficacy and effectiveness of LAIV.…”
Section: Immunogenicitycontrasting
confidence: 43%
“…In one study conducted in Turkey, influenza vaccination significantly reduced acute otitis media in children by 50.9% compared to unvaccinated controls and by inference antibiotic use in the vaccinated children. 34 A study conducted in Canada demonstrated convincingly that influenza associated antibiotic prescriptions declined by ∼64% after introduction of universal influenza vaccination in Ontario compared to other Canadian provinces that limited the use of influenza vaccines to populations most at risk for disease. 35 The second mechanism by which viral vaccines can reduce AMR is by prevention of inappropriate antibiotic prescriptions for respiratory tract infections caused by viral pathogens.…”
Section: Impact Of Viral Vaccines On Amrmentioning
confidence: 99%